Effect of unprotected interior beams on membrane behaviour of composite floor systems in fire, I : experimental investigation - Tan, Kang Hai (2013)
A number of previous studies on tensile membrane action have been conducted and they are very valuable towards understanding the behaviour of isolated slabs as well as of floor assemblies. However, the role of unprotected interior beams in the development of TMA still has not clearly determined. This paper presents an experimental study on the effect of unprotected interior beams on the behaviour of composite floor assemblies in fire. The experimental observations and results of two one-fourth scale composite slab-beam systems, 3.15 m by 3.15 m in plan, subjected to transient-heating test are presented. The test results show that the presence of interior beams can reduce the slab deflection and greatly enhance the slab load-bearing capacity. The interior beams have a major role in helping the slab in passing through the ‘transition’ stage, and thus the slab can mobilize more tensile membrane forces. Without the interior beams, the compressive ring failure may occur resulting in a little contribution from TMA in the slab load-bearing capacity.